2017
DOI: 10.1007/s13365-017-0584-2
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic mice expressing HIV-1 envelope protein gp120 in the brain as an animal model in neuroAIDS research

Abstract: HIV-1 infection causes injury to the central nervous system (CNS) and is often associated with neurocognitive disorders. One model for brain damage seen in AIDS patients is the transgenic (tg) mouse expressing a soluble envelope protein gp120 of HIV-1 LAV in the brain in astrocytes under the control of the promoter of glial fibrillary acidic protein. These GFAP-gp120tg mice manifest several key neuropathological features observed in AIDS brains, such as decreased synaptic and dendritic density, increased numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 124 publications
(229 reference statements)
0
29
0
Order By: Relevance
“…As stated in the regulation of GFAP expression, IL-6 cytokine family member and JAK2/STAT3 cascade can form a positive feedback loop, in which increased GFAP expression during astrogliosis also increases the production of IL-6 cytokine family member, thereby worsening the inflammatory reactions. In addition, GFAP transgenic studies showed that HIV-1 gp120 coater proteins are neurotoxic to the GFAP gene and can cause hydrocephalus in mice (Brenner, 1994) as well as other disorders (Thaney et al, 2018). These findings have been substantiated by clinical observations.…”
Section: Inflammationmentioning
confidence: 88%
“…As stated in the regulation of GFAP expression, IL-6 cytokine family member and JAK2/STAT3 cascade can form a positive feedback loop, in which increased GFAP expression during astrogliosis also increases the production of IL-6 cytokine family member, thereby worsening the inflammatory reactions. In addition, GFAP transgenic studies showed that HIV-1 gp120 coater proteins are neurotoxic to the GFAP gene and can cause hydrocephalus in mice (Brenner, 1994) as well as other disorders (Thaney et al, 2018). These findings have been substantiated by clinical observations.…”
Section: Inflammationmentioning
confidence: 88%
“…HIV gp120 is a potent neurotoxin (Kim et al, 2011;Meucci and Miller, 1996;Zhou et al, 2017) that has been measured in the brains of patients with HAND (Jones et al, 2000). HIV gp120 evokes synaptic and behavioral deficits in vivo that mimic significant aspects of HAND (Thaney et al, 2018;Toggas et al, 1994). In this study, we used a cell culture model to study changes in tonic inhibition during exposure to the neuroinflammatory stimulus gp120.…”
Section: Introductionmentioning
confidence: 99%
“…Neurogenesis is important to study in the context of HAND, because HIV-1 virions have been found in the hippocampal formation of pediatric AIDS patients [ 18 ], and impaired neurogenesis has been observed in both HIV-1-infected patients and SIV-infected macaques [ 19 , 20 ], as well as glial fibrillary acidic protein (GFAP)-driven gp120 transgenic mice [ 21 25 ] and GFAP-Tat transgenic mice [ 26 , 27 ]. More importantly, NSCs have been shown to be targets of active HIV-1 infection [ 25 , 27 32 ].…”
Section: Introductionmentioning
confidence: 99%